Traditional Use, Phytochemicals and Pharmacological Activity of Salvadora persica: A Review - Kumar, Dharmendra; Sharma, Pramod K. (Current Nutrition & Food Science, 2021)
Salvadora persica L., also known as Miswak, Peelu and Arak, is used traditionally as a source of food, cosmetics, fuel and medicine. The most common traditional use of Salvadora persica sticks is tooth cleaning. Other traditional uses of Salvadora persica are in diabetes, arthritis, constipation, fever, cold, malaria, viral infection, gonorrhea, worms, antidotes, stimulators, laxatives and various veterinary problems, such as poor milk production, abdominal disorder, diarrhea, etc. Now traditional uses of Salvadora persica have been scientifically proved in modern research. Various pharmacological activities of Salvadora persica as reported in modern research were anti- microbial, antifungal, anti-inflammatory, analgesic, antiulcer, anticonvulsant, antifertility, wound healing, anthelmintic, antidepressant, anticancer, etc. These pharmacological activities are due to the presence of many phytochemicals in Salvadora persica. Phytochemicals present in Salvadora persica are alkaloids, glycosides, tannins, flavonoids, proteins, terpenoids and sterols. The aim of this review is to provide various traditional use of Salvadora persica proved by modern research, and highlight its pharmacological activity and phytochemicals. This review article may be used to set a new research hypothesis with reference to traditional use.
Keywords: miswak